2020
DOI: 10.1021/acs.jpcc.0c06581
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Potential of Amorphous Silica Surfaces for the Removal of Phenol from Biofuel: A Density Functional Theory Investigation

Abstract: Biofuels may contain phenolic molecules, which are toxic for humans and can significantly affect engine performance. In this context, amorphous silica surfaces are attractive since they have the potential to separate the harmful molecules from the biofuel constituents through a selective adsorption process. Here, density functional theory is employed to describe the different adsorption modes of toluene and phenol, chosen as model molecules, on amorphous silica surfaces with various silanol densities. It is fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…[10][11][12] Furthermore, investigations into the production of green hydrogen, required for this methanol production, have been carried out via DFT 13,14 and molecular dynamics. 15,16 There is no shortage of publications utilizing these computational tools for a variety of other climate-relevant processes, such as CO 2 absorption with metal-organic frameworks, 17,18 recycling of chlorine for polyvinyl chloride production, 19,20 biofuel production, 21,22 and material discovery. 23 Additionally, Jain et al 24 provided a comprehensive review of the application of DFT for energy materials like batteries, photovoltaics, and capacitors.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Furthermore, investigations into the production of green hydrogen, required for this methanol production, have been carried out via DFT 13,14 and molecular dynamics. 15,16 There is no shortage of publications utilizing these computational tools for a variety of other climate-relevant processes, such as CO 2 absorption with metal-organic frameworks, 17,18 recycling of chlorine for polyvinyl chloride production, 19,20 biofuel production, 21,22 and material discovery. 23 Additionally, Jain et al 24 provided a comprehensive review of the application of DFT for energy materials like batteries, photovoltaics, and capacitors.…”
Section: Introductionmentioning
confidence: 99%
“…While silica supports are generally considered inert, it has been shown that chemisorption of alcohols readily occurs at defect sites that are formed when silica ruptures during milling (Figure S11). In addition to chemisorbed phenolates on such defect sites, phenol can physisorb onto silanol sites. The physisorbed phenols are more easily removed and comprise most of the phenol yield that was observed after washing. This ultimately suggests that the Lewis acid site concentration plays a minor role in absorption.…”
mentioning
confidence: 99%